Mixed powder for pasty brazing material and pasty brazing material using mixed powder for pasty brazing material
By using a mixed powder of brazing material powder and a cellulose-based resin powder, the problem of prone to agglomeration in the manufacturing process of water-soluble binder is solved, and efficient manufacturing and stable viscosity of paste-like brazing materials are achieved, ensuring good coating workability and brazing quality.
Patent Information
- Application Number
- CN202380068550.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-11-04
- Filing Date
- 2023-11-02
- Publication Date
- 2025-04-25
AI Technical Summary
When manufacturing water-soluble binder, agglomeration is prone to occur, resulting in limited speed of manufacturing paste-like brazing materials and unstable viscosity of the binder.
A new paste brazing material is developed, by using a mixed powder of a brazing material powder and a cellulose-based resin powder, the manufacturing process of the binder is omitted, and the viscosity of the paste brazing material is controlled by adjusting the ratio of water and organic solvent.
The generation of agglomerations is effectively suppressed, the manufacturing process is simplified, the viscosity stability of the paste-like brazing material is improved, and good coating workability and brazing quality are ensured.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to a raw material powder for a paste solder used in joining stainless steel and the like, and a paste solder manufactured using the raw material powder. Background Art
[0002] Conventionally, in joining stainless steel, particularly in cases where corrosion resistance is required, a brazing material mainly composed of nickel, iron, and cobalt has been applied, and joining has been performed by furnace brazing. Also, as the coating method of the brazing material, methods such as pre-placed solder (Japanese: 置きろう) using an amorphous foil, dispenser coating of paste solder, screen printing, and powder sprinkling printing method have been used. In particular, in order to suppress the coating amount of the brazing material, a coating method using paste solder has been adopted.
[0003] This paste solder is obtained by kneading a brazing material powder and a binder, and requires three processes: brazing material powder manufacturing, binder manufacturing, and paste manufacturing. For example, the paste solder shown in Patent Document 1 can be cited.
[0004] Prior Art Documents
[0005] Patent Documents
[0006] Patent Document 1: Japanese Patent No. 3228849 Summary of the Invention
[0007] Problems to be Solved by the Invention
[0008] As the binder for the paste solder, hydrophobic (oil-based) and water-soluble binders are used. The water-soluble binder that does not require a working environment and explosion-proof equipment has a low environmental load and is preferred. However, in the manufacturing process of the water-soluble binder, when a water-soluble resin that becomes a thickener is dissolved in an aqueous solution, lumps called agglomerates (a mass in which only the outer surface of powder particles and their aggregates is hydrated to form a viscous gel layer that hinders the penetration of water to the inside) are generated. Before the water-soluble binder becomes stable, strong stirring, long-time stirring, or a long-time dispersion period is required, which limits the speed of manufacturing the paste solder. In addition, due to the generation of agglomerates and the volatilization of moisture during manufacturing, there are also problems such as unstable viscosity of the binder.
[0009] Means for Solving the Problems
[0010] The present inventors have developed a new paste solder that suppresses the generation of agglomerates and can omit the binder manufacturing process, and a mixed powder for paste solder used in the paste solder.
[0011] Specifically, the mixed powder for cream solder of the present invention is characterized by comprising solder material powder and resin powder as a water-soluble thickener, wherein the mass ratio of the solder material powder:the resin powder is 99.88 to 97.90:0.12 to 2.10.
[0012] Furthermore, the present invention is characterized in that the resin powder as the thickener is preferably a cellulose-based resin powder, and the resin powder is one or two selected from methyl cellulose, carboxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, hydroxypropyl methyl cellulose and the like.
[0013] The cream solder of the present invention can be obtained by mixing 8.0 to 26.6 parts by mass of water with 100 parts by mass of the mixed powder for the cream solder.
[0014] The paste solder of the present invention can also be obtained by kneading 100 parts by mass of the mixed powder for the paste solder with 7.8 parts by mass or less in total (excluding the case where the total amount of the organic solvent described below is 0 parts by mass) of one to three kinds (hereinafter referred to as organic solvents) selected from acetone, methanol, ethanol, n-propanol, isopropanol, ethylene glycol, and glycerol, and 2.0 to 20.0 parts by mass of water, in which case the total amount of water and the organic solvent is 8.0 to 22.0 parts by mass.
[0015] Alternatively, the paste solder of the present invention can also be obtained by kneading 100 parts by mass of the mixed powder for the paste solder with 1.0 parts by mass or less (excluding the case where the total amount is 0 parts by mass) of one or two of polyvinyl alcohol, urethane resin, acrylic resin, and vinyl acetate as water as a water-soluble resin, in which case the total amount of water and the water-soluble resin is 8.0 to 22.0 parts by mass.
[0016] In addition, the paste solder of the present invention comprises any one to three of acetone, methanol, ethanol, n-propanol, isopropanol, ethylene glycol, and glycerol in an amount of 7.8 parts by mass or less (excluding the case where the total amount of the organic solvent is 0 parts by mass) as an organic solvent, and one or two selected from polyvinyl alcohol, urethane resin, acrylic resin, and vinyl acetate in an amount of 1.0 parts by mass or less (excluding the case where the total amount of the organic solvent is 0 parts by mass) as a water-soluble resin, with the remainder being water, and the total amount of water, organic solvent, and water-soluble resin being 8.0 to 22.0 parts by mass. It should be noted that the remainder of water is preferably 2.0 to 20.0 parts by mass.
[0017] It should be noted that when manufacturing the paste solder of the present invention, it is preferred that the above-mentioned polyvinyl alcohol, urethane resin, acrylic resin, and vinyl acetate are not solid substances, but aqueous solution substances are diluted with water for use. As the aqueous solution, for example, a solution having a solid content of 50% or less such as polyvinyl alcohol having a solid content of about 10% by mass, a urethane resin having a solid content of about 30% by mass, and vinyl acetate having a solid content of about 40% by mass can be used.
[0018] Furthermore, since the paste solder of the present invention is a solder material used for furnace soldering of stainless steel, the solder material powder is preferably a solder material containing any one of nickel, iron, and cobalt as a main component.
[0019] Furthermore, the solder material powder contained in the mixed powder for solder cream of the present invention is preferably an alloy powder produced by an atomization method, and the particle size thereof is preferably 250 μm or less.
[0020] In order to suppress sedimentation of the solder powder in the cream solder of the present invention, the particle size of the solder powder is preferably 150 μm or less, more preferably 63 μm or less.
[0021] Next, the reasons for limiting the components and blending ratio of the mixed powder for cream solder of the present invention and the cream solder using the same will be described.
[0022] The water-soluble thickener in the mixed powder for paste solder of the present invention has the effect of inhibiting the sedimentation and separation of the solder material powder. However, if the amount is less than 0.12 parts by mass in 100 parts by mass of the mixed powder for paste solder, the thickening effect is weak and the solder material powder settles. If it exceeds 2.10 parts by mass, the viscosity of the paste solder increases, which impairs the coating workability. In addition, in the soldering process, the amount of decomposition gas of the resin increases, causing poor soldering. Therefore, the amount of water-soluble thickener added is limited to the range of 0.12 to 2.10 parts by mass.
[0023] The water-soluble thickener is preferably a cellulose-based thickener that suppresses sedimentation and separation of the solder material powder. However, any thickener other than a cellulose-based thickener may be used as long as it is a water-soluble powdery thickener.
[0024] When the mixed powder for solder paste of the present invention is used and only water is added to prepare solder paste, when the amount of water added relative to 100 parts by mass of the mixed powder for solder paste is less than 8.0 parts by mass, the viscosity of the solder paste is high, which impairs the coating workability. In addition, if it exceeds 26.6 parts by mass, the viscosity of the solder paste becomes low, the solder material powder is easy to precipitate, and the coating workability is impaired. Therefore, the amount of water in the solder paste is limited to the range of 8.0 to 26.6 parts by mass.
[0025] The addition of organic solvents can not only achieve compatibility even when grease adheres to the stainless steel of the base material, but also adjust the anti-corrosion effect of the paste, quick-drying properties or slow-drying properties. Since the thickener is water-soluble, a water-soluble organic solvent can be selected, which may include 1 to 3 selected from acetone, methanol, ethanol, n-propanol, isopropanol, ethylene glycol, and glycerol. In addition, when an organic solvent is added to the paste, as described above, the total amount of water and organic solvent is preferably in the range of 8.0 to 22.0 parts by mass relative to 100 parts by mass of the mixed powder for the paste solder. At this time, when the amount of water added is less than 2.0 parts by mass and the total amount of organic solvent exceeds 7.8 parts by mass, the amount of water reacting with the water-soluble thickener decreases, the viscosity of the paste solder is unstable, and the solder material powder is easy to precipitate, which impairs the coating workability. Therefore, the amount of water added is limited to the range of 2.0 to 20.0 parts by mass, and the total amount of the organic solvent added is limited to the range of 7.8 parts by mass or less.
[0026] In addition, in order to improve the effect of suppressing the sedimentation and separation of the brazing material powder and improve the adhesion to the base material stainless steel, the paste brazing material of the present invention may contain one or two selected from water-soluble polyvinyl alcohol, urethane resin, acrylic resin, and vinyl acetate. However, if the amount added relative to the paste exceeds 1.0 parts by mass, the amount of decomposition gas generated during the brazing process increases, causing poor brazing, so the amount added to the paste is limited to a range of less than 1.0 parts by mass. In the case of adding a water-soluble resin to the paste, the total amount of water and the water-soluble resin is preferably in the range of 8.0 to 22.0 parts by mass relative to 100 parts by mass of the mixed powder for the paste brazing material. In addition, in the case of a paste brazing material comprising water, an organic solvent and a water-soluble resin, as described above, the total amount of water, an organic solvent and a water-soluble resin is preferably in the range of 8.0 to 22.0 parts by mass. DETAILED DESCRIPTION
[0027] The mixed powder for the paste solder of the present invention can be obtained by homogeneously mixing a brazing material powder produced by an atomization method and adjusted to a specified particle size, for example, BNi-1 to BNi-13 and BCo-1 shown in "JIS Z 3265 Nickel Brazing Filler" and "AWS A5.8 Specification for Filler Metals for Brazing and Braze Welding", and a developed material shown in Japanese Patent No. 3354922, Japanese Patent No. 5269888, Japanese Patent No. 5783641, and Japanese Patent No. 5858512, with a water-soluble thickener at a specified ratio using a V-type mixer or the like. The brazing material powder in the present invention is preferably a Ni-based heat-resistant brazing material described in Japanese Patent No. 3354922, which contains, by weight%, 25 to 35% Cr, 4 to 8% P, 3 to 6% Si, 9 to 11.5% P+Si in total, and the remainder consisting of Ni and inevitable impurities.
[0028] Furthermore, a solution obtained by adding a predetermined amount of water or an organic solvent to the mixed powder for cream solder is kneaded using a kneading machine (mixer) or the like to obtain a cream solder using the mixed powder for cream solder of the present invention.
[0029] By adjusting the amount of the water-soluble thickener in the mixed powder for the paste solder, the amount of water and the amount of the solution in the paste solder produced using the water-soluble thickener, the viscosity of the paste solder suitable for the target coating method can be obtained, and it can be used for dispenser coating, screen printing, metal masking, dipping, etc. In particular, by adjusting the viscosity of the paste solder to 100 to 1500 dPa·s, good coating workability can be obtained.
[0030] Example
[0031] The brazing material paste was prepared according to the above procedure so as to have the mixing ratio shown in Table 1. Then, after kneading, it was added to a sealed container and stored at 25°C for 12 hours. Then, the viscosity of the paste was confirmed using Viscotester VT-06 manufactured by RION Corporation (using rotor No. 2, rotor speed 62.5 rpm).
[0032] In addition, it was checked whether the brazing material powder was precipitated in the sealed container.
[0033] Regarding the paste viscosity, a range of 100 to 1500 dPa·s was considered acceptable in consideration of coating workability, and no precipitation of solder material powder was considered acceptable 12 hours after the paste was prepared.
[0034] The mixing ratios of Examples and Comparative Examples, the viscosity of the pastes, and the precipitation conditions of the brazing material powder are shown in Table 1. As the brazing material powder, Ni-29Cr-6P-4Si alloy powder described in Japanese Patent No. 3354922 was used.
[0035] [Table 1]
[0036]
[0037] The paste viscosity of Examples No. 1 to No. 11 was in the range of 100 to 1500 dPa·s, and no precipitation of solder material powder was observed. On the other hand, the thickener blended in Comparative Example No. 12 was less than 0.12 parts by mass, the thickener blended in Comparative Example No. 13 was more than 2.10 parts by mass, the organic solvent blended in Comparative Example No. 14 was more than 7.8 parts by mass, and the vinyl acetate blended in Comparative Example No. 15 was more than 1.0 parts by mass, and the paste viscosity was out of the target range of 100 to 1500 dPa·s, or precipitation of solder material powder was observed. It should be noted that no agglomeration was observed in the Examples and Comparative Examples using the pastes prepared by the present invention.
[0038] In addition, the suppression of the generation of agglomerates and the number of days for producing the cream solder were evaluated by the production process of the present invention. The results are shown in Table 2.
[0039] [Table 2]
[0040]
[0041] Example No. A shows the production details of Example No. 2 described in Table 1. Except for the production and adjustment of the mixed powder for cream solder (step I), the paste production steps (step II and step III) required one day.
[0042] In contrast, in the case of Comparative Example No. B, in which a thickener is added to the powder for paste solder with the same ingredients as in Example No. 2 but not mixed, the number of days required for the paste manufacturing process (the total of process II and process III) is 1 day, as in Example No. A, but agglomeration occurs in process III of paste manufacturing, and it becomes a state that cannot be used as paste solder. In addition, in Comparative Examples No. C and No. D, which are conventional processes for manufacturing paste solder, the number of days required for the paste manufacturing process (the total of process II and process III) of Comparative Example No. C, in which long-term stirring is performed in process II of binder manufacturing, is 3 days in total, and the manufacturing time is longer than that of the present invention. In addition, it is confirmed that the moisture of the binder evaporates in process II, and the viscosity of the binder increases, so there is a tendency for the viscosity of the paste solder to increase, and the viscosity of the paste is unstable. Therefore, in Comparative Example No. D, in which stirring was performed for a short time in order to suppress the volatilization of water in Step II of manufacturing the binder, agglomerates were generated in Step II of manufacturing the binder, and it took 5 days to disperse them. The viscosity of the paste solder was equivalent to that of Example No. A, but the number of days for the paste manufacturing process (the total of Step II and Step III) was 7 days, which was a long time.
[0043] That is, it can be said that the method for producing a cream solder of the present invention is more effective than the conventional method for producing a cream solder in terms of the generation of lumps, the number of days for production, and the viscosity stability of the cream solder.
[0044] Industrial Applicability
[0045] As described above, the mixed powder for solder paste of the present invention and the solder paste using the same can obtain a solder paste having a viscosity suitable for application of solder paste, no precipitation of solder material powder, and excellent coating workability. In addition, for the manufacture of solder paste, it is expected to be a new paste preparation method that can simplify the binder manufacturing process.
Claims
1. A mixed powder for paste solder, characterized in that: The invention comprises soldering material powder and resin powder as a water-soluble thickener, wherein the mass ratio of the soldering material powder to the resin powder is 99.88-97.90:0.12-2.
10.
2. The mixed powder for cream solder according to claim 1, characterized in that: The brazing material powder is an alloy powder containing any one of nickel, iron, and cobalt as a main component and produced by an atomization method.
3. The mixed powder for cream solder according to claim 1 or 2, characterized in that: The resin powder is cellulose-based.
4. The mixed powder for cream solder according to claim 1 or 2, characterized in that: The resin powder is one or two selected from methyl cellulose, carboxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose and hydroxypropyl methyl cellulose.
5. The mixed powder for cream solder according to claim 1 or 2, characterized in that: The brazing material powder has a particle size of 250 μm or less.
6. A paste solder, characterized in that: 8.0 to 26.6 parts by mass of water are blended with respect to 100 parts by mass of the mixed powder for cream solder according to claim 1 or 2.
7. A paste solder, characterized in that: The mixed powder for cream solder according to claim 1 or 2 contains 7.8 parts by mass or less of one to three selected from acetone, methanol, ethanol, n-propanol, isopropanol, ethylene glycol, and glycerin as organic solvents, and 2.0 to 20.0 parts by mass of water, wherein the total amount of water and the organic solvent is 8.0 to 22.0 parts by mass, and The cream solder does not include a case where the total amount of the organic solvent is 0 parts by mass.
8. A paste solder, characterized in that: The mixed powder for paste solder according to claim 1 or 2 contains 1.0 parts by mass or less of one or two selected from polyvinyl alcohol, urethane resin, acrylic resin, and vinyl acetate as water-soluble resins, the remainder being water, and the total amount of water and the water-soluble resin is 8.0 parts by mass to 22.0 parts by mass, and The above-mentioned cream solder does not include a case where the total amount of the water-soluble resin is 0 parts by mass.
9. A paste solder, characterized in that: The mixed powder for paste solder according to claim 1 or 2 comprises 7.8 parts by mass or less of one to three selected from acetone, methanol, ethanol, n-propanol, isopropanol, ethylene glycol, and glycerol as organic solvents, and 1.0 parts by mass or less of one or two selected from polyvinyl alcohol, urethane resin, acrylic resin, and vinyl acetate as water-soluble resins, with the remainder being water, and the total of water, organic solvent, and water-soluble resin is 8.0 parts by mass to 22.0 parts by mass, and The cream solder does not include a case where the total amount of the organic solvent is 0 parts by mass, and a case where the total amount of the water-soluble resin is 0 parts by mass.
10. A method for producing a paste solder, characterized in that: The method comprises the step of mixing 8.0 to 26.6 parts by mass of water with 100 parts by mass of the mixed powder for cream solder according to claim 1 or 2.
11. A method for producing a paste solder, characterized in that: The method comprises the steps of mixing 100 parts by mass of the mixed powder for cream solder according to claim 1 or 2 with 7.8 parts by mass or less of one to three selected from acetone, methanol, ethanol, n-propanol, isopropanol, ethylene glycol, and glycerin as an organic solvent, and 2.0 to 20.0 parts by mass of water, wherein the total amount of water and the organic solvent is 8.0 to 22.0 parts by mass, and The method for producing the cream solder does not include the case where the total amount of the organic solvent is 0 parts by mass.
12. A method for producing a paste solder, characterized in that: The method comprises the steps of mixing 100 parts by mass of the mixed powder for cream solder according to claim 1 or 2 with a total of 1.0 parts by mass or less of one or two selected from polyvinyl alcohol, urethane resin, acrylic resin, and vinyl acetate as a water-soluble resin, and water, wherein the total amount of water and the water-soluble resin is 8.0 to 22.0 parts by mass, and The method for producing the cream solder does not include the case where the total amount of the water-soluble resin is 0 parts by mass.
13. A method for producing a paste solder, characterized in that: The method comprises the steps of mixing 100 parts by mass of the mixed powder for cream solder according to claim 1 or 2 with a total of 7.8 parts by mass or less of one to three selected from acetone, methanol, ethanol, n-propanol, isopropanol, ethylene glycol, and glycerol as organic solvents, a total of 1.0 parts by mass or less of one or two selected from polyvinyl alcohol, urethane resin, acrylic resin, and vinyl acetate as water-soluble resins, and water, wherein the total amount of water, the organic solvent, and the water-soluble resin is 8.0 parts by mass% to 22.0 parts by mass%, and The method for producing the cream solder does not include the case where the total amount of the organic solvent is 0 parts by mass and the case where the total amount of the water-soluble resin is 0 parts by mass.
Citation Information
Patent Citations
Apparatus for production of ozone
JP1977069888A
Fuel injector
JP1982083641A
Optical connector with bush
JP1983058512A